2010
DOI: 10.1111/j.1469-0691.2009.03037.x
|View full text |Cite
|
Sign up to set email alerts
|

An open randomized controlled trial of desmopressin and pulse dexamethasone as adjunct therapy in patients with pulmonary involvement associated with severe leptospirosis

Abstract: Pulmonary involvement in leptospirosis is emerging as a common complication of severe leptospirosis. A prospective randomized controlled trial of desmopressin or high-dose (pulse) dexamethasone as adjunctive therapy in 68 patients with pulmonary involvement associated with severe leptospirosis was conducted between July 2003 and October 2006 at five hospitals in Thailand. There were 23 patients in the desmopressin group, 22 in the pulse dexamethasone group, and 23 in a control group who received standard criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 16 publications
0
28
0
2
Order By: Relevance
“…1 Similarly, controlled trial of steroids to treat leptospirosis showed no benefit to patient outcome. 38 Steroids should be reserved for patients that have a clinical condition for which they have reproducibly been shown to be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…1 Similarly, controlled trial of steroids to treat leptospirosis showed no benefit to patient outcome. 38 Steroids should be reserved for patients that have a clinical condition for which they have reproducibly been shown to be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…A Sri Lankan study showed a significant reduction in mortality rates with methyl prednisolone in severe cases of leptospirosis (Kularatne et al ., 2011). However, a recent prospective randomized controlled trial, involving 68 patients with severe leptospirosis with pulmonary complications, showed no significant benefit from using steroids (Niwattayakul et al , 2010). In this review, three of our patients showed significant clinical improvement after the administration of steroids, as described previously.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 High doses or a pulse of dexamethasone or methylprednisolone have been used in patients with severe lung involvement in leptospirosis. 14,16,17 In a series of 30 patients, Shenoy et al demonstrated that corticosteroids reduce mortality and change outcomes significantly. 14 Trivedi et al found that mortality was higher in patients with pulmonary involvement who did not receive steroids and concluded that high dose glucocorticoids should be given as early as possible after the onset of dyspnoea to all the patients with pulmonary involvement.…”
Section: Discussionmentioning
confidence: 99%